How to read and Interpret GC/MS Spectra - Nugraha, Adam; Nandiyanto, Asep Bayu Dani (Universitas Pendidikan Indonesia (UPI), 2021)
Gas chromatography mass spectrometry (GC/MS) analysis is used as analytical tool for volatile and complex mixture samples. Its effectivity and sensitivity to detect the analyte components make it applicable in a wide range of purposes. This technique can be used to conduct quantitative as well as qualitative analysis. Unfortunately, very few, if there are, of publications dedicate the research to give an explanatory report using a step-by-step approach on how to read and interpret the analysis result. Thus, this study is aimed to fulfill the gap on bridging the spectra data output of GC/MS measurement into the light of easy way reading and interpreting its spectra. The research method used both library spectra matching and a priory spectra interpretation on chosen compound samples. The general guideline and application are discussed.